A New Species of Tillandsia (Bromeliaceae) from Colombia related to Tillandsia paraensis Mez. - Takizawa, Hiroyuki; Gouda, Eric J. (Phytotaxa, 2025)
A new species of Tillandsia from San José del Guaviare, Guaviare, Colombia, is described and illustrated. This new species is related to Tillandsia paraensis Mez and is morphologically compared with this species.